Comparative Analysis of the Nonoperative Treatment of Elbow Ulnar Collateral Ligament Injuries in Professional Baseball Players with and without Platelet-Rich Plasma. Issue 7 (30th July 2018) - McQueen, Peter Douglas; Camp, Christopher L.; Chauhan, Aakash; Erickson, Brandon J.; Potter, Hollis G.; D'Angelo, John; Fealy, Stephen; Ciccotti, Michael G.; Fronek, Jan
Objectives: In the setting of ulnar collateral ligament (UCL) injury, surgical reconstruction of the UCL is not always selected, as it leads to a prolonged recovery time and return to play rates between 67-95%. To date, there is limited data on outcomes following nonoperative treatment in this population. Orthobiologics, such as platelet-rich plasma (PRP), have recently been used as an adjunct therapy for standard nonoperative treatment including rest and physical therapy for UCL injuries. The objective of this study was to determine if the addition of PRP injections in professional baseball players with UCL injuries reduces recovery time, lowers the likelihood of surgery, and increases the return to play rate compared to traditional nonoperative treatment. Methods: The Health and Injury Tracking System (HITS) database was searched from 2011-2015 for Major and Minor league baseball players with Grade I, II or III UCL injuries. Standard demographic, injury, and return to play data was obtained for all players. MRI's for 353 athletes were reviewed by a musculoskeletal radiologist and graded accordingly. Outcomes were compared between players who received PRP injections in addition to traditional nonoperative treatment (PRP group) and players who received traditional nonoperative treatment alone (No PRP group). Statistical analysis was performed using Student's T-test and Chi-square for parametric data. Kaplan Meier's analysis was used for estimating longevity of the treatment. Results: A total of 544 Major and Minor League Baseball players with UCL tears underwent an initial course of nonoperative treatment (active rest & rehabilitation) for their injury between 2011-2015. Of these, 133 underwent PRP injections plus rehab and 411 underwent rehab alone. There was a significantly higher proportion of Major League Baseball players in the PRP group compared to the No PRP group (25.6% vs 9.0%, P<0.001). There was no difference between the two cohorts in regard to the grade of UCL tear (Figure 1). The players in the PRP group had a significantly longer time before returning to a throwing program compared to the No PRP group (64 days vs 51 days, P<0.001). The mean time from injury date to PRP injection was 14.5 days, which may explain the difference in time to return to throwing. The return to play rate in a live game without surgery was significantly lower in the PRP group compared to the No PRP group (46% vs 57%, P=0.03). There was no difference in the proportion of athletes requiring UCL reconstruction (58% vs 51%) or the time to surgery (154 days vs 178 days) between the two groups. Kaplan Meier survivor analysis showed no difference between the PRP and No PRP groups with regard to longevity of the native UCL (Figure 2). Conclusion: Among Major and Minor League Baseball players who were treated nonoperatively for a UCL injury between 2011-2015, 24% underwent PRP injections prior to rehab. Compared to traditional nonoperative rehab alone program, players who received PRP injections experienced a significantly longer time before returning to throwing, which may be in part due to the delay between the injury date and PRP injection. PRP injections did not appear to have a significant effect on the likelihood of surgical intervention.